THE EFFECTS OF TASK-BASED INSTRUCTION AND LEXICAL INVOLVEMENT LOAD ON THE DURABILITY OF VOCABULARY COMPREHENSION - Kuvandikova Sarvinoz (Scholar Express Journal, 2025)
Vocabulary durability—how well learners remember and interpret lexical elements over time—is still a major topic in second language acquisition (SLA). This research examines empirical and theoretical perspectives on how taskbased instruction (TBI) and lexical involvement load (IL) influence the durability of vocabulary understanding. Drawing on the Involvement Load Hypothesis (Laufer & Hulstijn, 2001) and cognitive processing models, it contends that task-based designs might naturally provide the motivational and cognitive circumstances necessary for long-term lexical learning. Following a review of previous studies, a longitudinal experimental design is developed to investigate how different task types with differing participation loads affect word comprehension over a three-month period.
Keywords: Task-Based Learning; Involvement Load; Vocabulary Comprehension